2019
DOI: 10.7150/ijbs.29203
|View full text |Cite
|
Sign up to set email alerts
|

PSPH Mediates the Metastasis and Proliferation of Non-small Cell Lung Cancer through MAPK Signaling Pathways

Abstract: Growing evidence indicates that phosphoserine phosphatase (PSPH) is up-regulated and correlates with prognosis in multiple types of cancer. However, little is known about the roles of PSPH in NSCLC. Thus, the aim of the present study was to demonstrate the expression of PSPH in human NSCLC and reveal its biological functions and the underlying mechanisms. qRT-PCR, western blot and immunohistochemistry were used to assess the expression of NSCLC patient specimens and NSCLC cell lines. The functions of PSPH in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…Consistent with our findings, PSPH expression has also been shown to be increased in breast cancer [ 41 ] and colorectal cancer and correlate with enhanced invasion and metastasis [ 42 ]. Furthermore, PSPH has also been shown to be important for proliferation and metastasis of non-small–cell lung cancer and cutaneous squamous cell carcinoma [ 21 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, PSPH expression has also been shown to be increased in breast cancer [ 41 ] and colorectal cancer and correlate with enhanced invasion and metastasis [ 42 ]. Furthermore, PSPH has also been shown to be important for proliferation and metastasis of non-small–cell lung cancer and cutaneous squamous cell carcinoma [ 21 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, downstream genes (excluding WT1) that could be regulated by WT1-AS were investigated by RNA-sEq. Combined with the KEGG enrichment data and cluster analyzes, 10 genes (PSPH [34,35], PHGDH [36,37], GSTO2 [38], CACNA2D1 [39,40], FYN [41], MAOB [42,43], ANPEP [44,45], ITGA2 [46,47], CTSS [48] and PRKCA [49] were selected for further explorations in view of their close association with cancer progression and prognosis. Our RT-qPCR assay validated that PSPH, GSTO2, FYN, and PHGDH could be regulated by WT1-AS, but not WT1 in GSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with previous studies. Liao, Ge, et al (2019) reported that the downregulation of PSPH expression inhibited migration, invasion, and proliferation of nonsmall cell lung cancer cells. Bachelor et al (2011) reported that PSPH is highly induced in proliferative normal keratinocytes and in skin tumors, and knockdown of PSPH significantly reduced the proliferation of SCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…The most common pathway for PSPH to affect cancer is the serine synthesis pathway (Antonov et al, 2014, Sun et al, 2015). PSPH could mediate NSCLC cell proliferation and metastasis via the MAPK signaling pathway (Liao, Ge, et al, 2019). PSPH might be a molecular marker for the proliferation and metastasis of A549 cells by regulating the AKT/AMPK signaling pathway (Liao, Yu, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%